498 Investigating fall-related injury hospitalisations for older indigenous people in Australia. (1st September 2016) - Lukaszyk, C; Harvey, L; Close, J; Ivers, R
Abstract : Background: It is estimated that one in three people aged 65 years and above fall each year in Australia. Despite high injury rates across Australia's Indigenous population and worse general health outcomes for older age groups, little is known about the incidence, nature and outcomes of fall-related hospitalisations specifically in older Indigenous people. Methods: Linked hospitalisation and death records for individuals aged 50 years and over admitted to a hospital in New South Wales, Australia for a fall-related injury were analysed. Indigenous status was identified if reported on at least 50% of an individual's hospitalisation records. Descriptive statistics, age-standardised hospitalisation rates and rate-ratios (ARR) were calculated. Trends over time were analysed using negative binomial regression. Results: Of the 312, 785 fall-related injury hospitalisations, 0.7% reported to be Indigenous. Compared to non-Indigenous people, a higher proportion of Indigenous people were aged 50–55 years (23.7% vs 5.2%, p < 0.0001), admitted for a head injury (23.8% vs 19.0%, p < 0.0001) whilst a lower proportion were admitted for hip fracture (9.2% vs 18.4%, p < 0.0001). Age-adjusted 30 day mortality was lower for Indigenous people (1.9% vs 4.2%, p = 0.0002). Indigenous people had consistently lower hospitalisation rates for fall-related injury than non-Indigenous people (ARR 0.83; 95% CI: 0.78–0.87, p < 0.0001). However, fall injury rates for Indigenous people increased at a greater rate of 5.6% (95% CI: 3.6–7.6, p < 0.0001) per annum compared to 2.6% (95% CI: 2.1–3.1, p < 0.0001) per annum for non-Indigenous people. Conclusions: Although fall-related injury rates appeared to be relatively low in Indigenous patients, this study demonstrates that fall injury is rapidly becoming a growing issue for Australia's older Indigenous population.